Differentiated Thyroid Cancer in the Pediatric/Adolescent Population: Evolution of Treatment. Issue 7 (October 2019) - Remiker, Allison S.; Chuang, Janet; Corathers, Sarah; Rutter, Meilan M.; Rutter, Michael J.; Myer, Charles M.; Gelfand, Michael J.; Trout, Andrew T.; Geller, James I.
Abstract : Differentiated thyroid cancer (DTC) is the most common cancer in adolescents and young adults. In 2015, the American Thyroid Association published guidelines for management of pediatric DTC. We report our institutional experience and highlight changing practices and new opportunities. A retrospective analysis of all patients diagnosed with DTC from 2001 to 2016 was performed. Among 59 eligible patients, 31 (53%), 15 (25%), and 13 (22%) had low-risk, intermediate-risk, and high-risk disease, respectively. Half (15/31) of low-risk and all intermediate-risk/high-risk patients received radioactive iodine (I-131) ablation. For low-risk patients, average I-131 dose decreased from 80 to 42.05 mCi, and the percentage of patients who received I-131 decreased over time. Eleven of 16 patients with tumor genomic data were found to have somatic targetable (n=6) or germline (n=5) mutations. Persistent/recurrent disease was only present in high-risk (n=8) and intermediate-risk (n=1) patients. Two patients with iodine-refractory disease received trametinib to enhance radioiodine uptake. All patients were alive at follow-up (median, 5 y; range, 1 to 15 y). Coincident with the recent American Thyroid Association guidelines, the use of I-131 in low-risk patients has decreased over time in our practice. Tumor sequencing and cancer genetic evaluation may help redefine opportunities for treatment of high-risk patients and family counseling.